If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z-9=-10+4z
We move all terms to the left:
3z-9-(-10+4z)=0
We add all the numbers together, and all the variables
3z-(4z-10)-9=0
We get rid of parentheses
3z-4z+10-9=0
We add all the numbers together, and all the variables
-1z+1=0
We move all terms containing z to the left, all other terms to the right
-z=-1
z=-1/-1
z=1
| 0.06(6t-4)=0.36(t+4)-1.68 | | 2x+4(x+3)-2=22 | | 3=y3 | | 4(2x-41)=2x+36 | | 8+x/5=-32 | | 3(x-1)=90 | | 1-4=2(-2+x) | | 3x+5x+2=42 | | 3x−2=3x−2= 8x+88x+8 | | 9(r-86)=27 | | 90=(7x-10) | | 5r+20=10 | | 4(2x-1)=-2(3+16) | | 12-15x=-2=15x | | 10r-4=16 | | -5x=10=6x=3 | | -6x-8=-4x+7 | | 56=30-2x | | 6(z+8)=90 | | 5a=12a | | 8x-164=2x+36 | | 2+3.5g=4+3g | | 3x+2x-14=11 | | 21-4.50g=3 | | 8x-7x=-15 | | -6-3r=-2-r | | r/4-19=-16 | | 7=t+2t | | 3(x+2)-4x=2(x-9) | | -2x-20=32 | | 4x(x+2)=56 | | n-13=-26 |